2009
DOI: 10.1038/emboj.2009.69
|View full text |Cite
|
Sign up to set email alerts
|

RNA helicase module in an acetyltransferase that modifies a specific tRNA anticodon

Abstract: Post-transcriptional RNA modifications in the anticodon of transfer RNAs frequently contribute to the high fidelity of protein synthesis. In eubacteria, two genome-encoded transfer RNA (tRNA) species bear the same CAU sequence as the anticodons, which are differentiated by modified cytidines at the wobble positions. The elongator tRNA Met accepts an acetyl moiety at the wobble base to form N 4 -acetylcytidine (ac 4 C): an inherent modification ensures precise decoding of the AUG codon by strengthening CÀG base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(115 citation statements)
references
References 39 publications
3
111
1
Order By: Relevance
“…Changing the conserved lysine residue in the Walker A motif (P loop) of the Kre33 helicase domain to an alanine (K289A) (Fig 6B, 6C and 6D) leads to a ~90% reduction in 18S rRNA acetylation (Fig 6D) [16]. Notably, the corresponding lysine residue in the bacterial homolog of Kre33, TmcA (Fig 6C), has been shown to be indispensable for its ATPase-dependent helicase function [29]. How the helicase domain of Kre33 influences the acetylation reaction remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Changing the conserved lysine residue in the Walker A motif (P loop) of the Kre33 helicase domain to an alanine (K289A) (Fig 6B, 6C and 6D) leads to a ~90% reduction in 18S rRNA acetylation (Fig 6D) [16]. Notably, the corresponding lysine residue in the bacterial homolog of Kre33, TmcA (Fig 6C), has been shown to be indispensable for its ATPase-dependent helicase function [29]. How the helicase domain of Kre33 influences the acetylation reaction remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant NAT10/hALP (amino acids 164 -834) lacking the N-terminal domains had an ability to acetylate calf thymus histones in vitro in the presence of acetyl-CoA (without ATP), indicating that NAT10/hALP has a histone acetyltransferase activity that might promote hTERT transcription via decondensation of chromatin structure (45). However, based on the crystal structure of TmcA, the N-terminal domain of the recombinant NAT10/hALP that was missing from that construct contains a functionally important region (DUF1726) that constitutes the RNA helicase/ATPase domain required for the tRNA acetyltransferase activity (28,46). Therefore, it remains to be conclusively determined whether full-length NAT10 has an efficient and specific histone acetyltransferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that Rra1p has an RNA helicase domain that is essential for ac 4 C1773 formation, Rra1p might unwind the local duplex of helix 45 via its helicase activity to acetylate C1773. A similar mechanism was previously proposed based on a structural study of TmcA, which is responsible for ac 4 C formation in tRNA (46). To investigate the physiological significance of ac 4 C modification in 18 S rRNA, we asked whether rRNA processing might be controlled by cellular energy status.…”
Section: Discussionmentioning
confidence: 99%
“…According to the crystal structure of E. coli TmcA (16), the RNA helicase domain contains ADP (a hydrolysis product of ATP), whereas the N-acetyltransferase domain interacts with acetyl-CoA. Biochemical and genetic studies of E. coli TmcA revealed that both domains are required for ac 4 C formation in tRNA (15,16). Orthologs of tmcA are widely distributed among archaea and eukaryotes.…”
Section: Resultsmentioning
confidence: 99%